Upaya Preventif: Edukasi dari Pemerintahan untuk Mencegah Gelandangan dan Pengemis - Ainnisa, Intan Nur; Aulia, Syifa Siti (Universitas Cokroaminoto Yogyakarta, 2024)
The government has an important role in carrying out preventive efforts to prevent homelessness and beggars, one of which is in the Yogyakarta area through the Social Service. This study uses a phenomenological method with a qualitative approach to explore phenomena related to the preventive efforts of DIY social services to prevent homelessness and beggars through counseling and education. The aim of this article is to provide an overview of the activities of the DIY Social Service in implementing education to prevent homelessness and beggars by examining three things, namely planning, implementation and obstacles in implementing counseling and education as a form of preventive effort. In planning, the social service makes a plan by first identifying its objectives, analyzing its targets, preparing materials, planning scheduling, preparing presenters to deliver outreach and public education. Counseling and education to the community is carried out by the DIY social service through various media such as print media, electronic media, and through cultural media. DIY social services face several obstacles, budget constraints and lack of human resources. However, the DIY social service has a solution to face these obstacles by inviting and collaborating with other institutions and community leaders to help spread outreach and education to the community.